Pengaruh Kualitas Sumber Daya Manusia,Sistem Pengendalian Internal, dan Partisipasi Anggota terhadap Kinerja Koperasi pada Koperasi Pegawai Negeri Kabupaten Buleleng - Manuaba, Ida Bagus Krisnayana; Darmawan, Nyoman Ari Surya (Vokasi : Jurnal Riset Akuntansi, 2023)
This study aims to (1) determine the effect of the quality of human resources on the performance of cooperatives in civil servant cooperatives in Buleleng Regency. (2) Knowing the Effect of Internal Control Systems on Cooperative Performance in Cooperative Civil Servants of Buleleng Regency. (3) Knowing the Effect of Member Participation on Cooperative Performance in Cooperative Civil Servants of Buleleng Regency. The research that will be used in this research is quantitative research. Data collection was carried out by distributing questionnaires and then the data was processed using the SPSS application. The collected data will be tested by descriptive statistical analysis, instrument test, classical assumption test and hypothesis test. The results of this study found that (1) The quality of human resources has a positive and significant effect on the performance of the Buleleng Regency civil servant cooperatives (2) Internal control has a positive and significant effect on the performance of the Buleleng Regency civil servant cooperatives (3) Member participation has a positive and significant effect on the performance of the Buleleng Regency civil servant cooperatives. significantly to the performance of civil servant cooperatives in Buleleng Regency.